Gender Equality Dimension in Nicaragua - Muhaimin Zulhair; Nadya Adha Ninggara (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2020)
One of the regions in the world that adhere to a fairly high patriarchal culture is Latin America. The role of women in the public sector does not play much because women tend to be oriented towards family responsibilities. However, the development of gender equality in the Latin America region has recently begun to develop and increase. One of the country in Latin America that have a good quality of gender equality based on Global Gender Gap Index is Nicaragua. Nicaragua become the 5th country with the best gender index in the world, and also become the best gender equality in the Latin America region. This research poses a question about what are the dimensions of gender equality in Nicaragua and how the country can gain this position based on those dimension despite the fact that human security and economic condition are still poor in Nicaragua? This research uses qualitative descriptive approach which analyze the secondary data gained from reliable sources. The results show that the health and education are the top dimensions of four dimensions (economy, politics, health, and education) used by Global Gender Gap Index. Furthermore, the high rank of political participation in Nicaragua has the historical roots since Sandinista as a movement and particularly when Sandinista took national power in 1980s and regained momentum in 2007.